2009
DOI: 10.1111/j.1365-2028.2009.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical traits involved in the genotypic variability to salt tolerance of Tunisian Cakile maritima

Abstract: Cakile maritima (family: Brassicaceae) was collected from three provenances belonging to different bioclimatic stages (humid, semi arid and arid) in Tunisia to study their eco‐physiological and biochemical responses to salinity. Seedlings were cultivated on inert sand for 20 days under NaCl treatments (0, 100, 200, 400 mm NaCl). Plant response to salinity was provenance‐ and salt‐dependent. At 100 mm NaCl, growth parameters (leaf biomass, area, number per plant and relative growth rate) were improved in plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
3
5
1
Order By: Relevance
“…These results support the hypothesis that the endogenously accumulated proline might have been contributed for ROS scavenging, having a protective effect that was manifested in a decline of lipid peroxidation, and thereby improving tolerance to seawater salinity stress. Our findings are congruent with several previous reports of positive correlations between the accumulation of proline in plants and reduced damage of proteins and membranes in several environmental stress conditions, including salinity (Alia, Saradhi, and Mohanty, 1997;Gunes et al, 2007;Hassine et al, 2008;Molinari et al, 2007;Ozden, Demirel,and Kahraman, 2009;Shevyakova, Bakulina, and Kuznetsov, 2009;Siripornadulsil et al, 2002;Wided et al, 2009;Yazici et al, 2007). A possible role for plant stress indicators such as proline and MDA accumulation levels in coastal ecological monitoring was further supported by the correlations found between those stress indicators and measures of dune topography and plant diversity previously reported as being connected to prevailing coastal dynamics Macedo et al, 2010).…”
Section: Discussion Ecophysiological Responses Of Dune Plants To Prevsupporting
confidence: 95%
See 3 more Smart Citations
“…These results support the hypothesis that the endogenously accumulated proline might have been contributed for ROS scavenging, having a protective effect that was manifested in a decline of lipid peroxidation, and thereby improving tolerance to seawater salinity stress. Our findings are congruent with several previous reports of positive correlations between the accumulation of proline in plants and reduced damage of proteins and membranes in several environmental stress conditions, including salinity (Alia, Saradhi, and Mohanty, 1997;Gunes et al, 2007;Hassine et al, 2008;Molinari et al, 2007;Ozden, Demirel,and Kahraman, 2009;Shevyakova, Bakulina, and Kuznetsov, 2009;Siripornadulsil et al, 2002;Wided et al, 2009;Yazici et al, 2007). A possible role for plant stress indicators such as proline and MDA accumulation levels in coastal ecological monitoring was further supported by the correlations found between those stress indicators and measures of dune topography and plant diversity previously reported as being connected to prevailing coastal dynamics Macedo et al, 2010).…”
Section: Discussion Ecophysiological Responses Of Dune Plants To Prevsupporting
confidence: 95%
“…Our study showed that lower levels of MDA were found in plants from foredunes submitted to prevailing transgressive dynamics, attaining the lowest value in plants harvested at the extreme transgressive Mira site. Furthermore, confirming previous reports (Hassine et al, 2008;Shevyakova, Bakulina, and Kuznetsov, 2009;Wided et al, 2009;Yazici et al, 2007), we found a significant negative correlation between the levels of proline and MDA accumulation across the surveyed sites. These results support the hypothesis that the endogenously accumulated proline might have been contributed for ROS scavenging, having a protective effect that was manifested in a decline of lipid peroxidation, and thereby improving tolerance to seawater salinity stress.…”
Section: Discussion Ecophysiological Responses Of Dune Plants To Prevsupporting
confidence: 93%
See 2 more Smart Citations
“…This slight non-alignment may be due to the different ecotype used in their experiments. In fact, in other reports a correlation between the Cakile maritima ecotype and the response to salinity regarding growth was found [ 18 , 35 , 36 , 37 ]. However, in our work, at high levels of salinity the RGR of Cakile maritima was reduced with respect to the control (by ca.…”
Section: Discussionmentioning
confidence: 92%